How does roughness kill adhesion? - Afferrante,L; Violano,G; Dini,D (Journal of the Mechanics and Physics of Solids, 2023)
It is well-known that adhesion is strongly influenced by surface roughness. Nevertheless, theliterature currently contains an ongoing debate regarding which roughness scales are primarilyresponsible for adhesion loss. In this study, we aim to contribute to this debate by conductingnumerical simulations on self-affine fractal profiles with varying fractal dimensions.Our results reveal that the long-wavelength portion of the roughness spectrum plays acrucial role in killing adhesion when considering profiles with Hurst exponent > 0.5.Conversely, for profiles with < 0.5, results show a different trend, indicating that adhesivestickiness is also influenced by short wavelength roughness. These findings are corroborated byour recent experimental observations. In such case, adhesive hysteresis and pull-off force exhibita continuous decrease with increasing roughness scales. However, for > 0.5, the pull-off forceconverges towards a finite value as the magnification increases.